Weed Seedbank Characterization in Long‐Term Cotton–Tomato Rotations in California. (1st March 2015) - Shrestha, Anil; Mitchell, Jeffrey P.; Hembree, Kurt J.
Abstract : This article characterizes the weed seedbank after a 12‐yr rotation of cotton ( Gossypium hirsutum L.)–tomato ( Lycopersicon esculentum L.) under standard tillage (ST) and conservation tillage (CT) with and without cover crops in Five Points, CA, from 1999 to 2011. Treatment comparisons included standard tillage with no cover crop (STNO), standard tillage with cover crop (STCC), conservation tillage with no cover crop (CTNO), and conservation tillage with cover crop (CTCC). Weed density, by species, in each plot was assessed in 2003, 2006, and 2011. In 2011, soil cores were taken from each plot and seedlings that emerged from these cores were monitored in the greenhouse, counted by species, and the data were subjected to canonical discriminant analysis. Differences in weed densities were not consistent between CT and ST plots but they were generally greater in plots with cover crops than in those without, particularly in the CT system. The seedbank size was largest in the CTCC system. The weed seedbank community composition of this system was also distinctly different from the other systems. Shepherd's‐purse ( Capsella bursa ‐ pastoris L. Medik.), black nightshade ( Solanum nigrum L.), henbit ( Lamium amplexicaule L.), and common chickweed ( Stellaria media L. Vill.) were associated with the CTCC system. Barnyardgrass ( Echinochloa crus‐galli L. Beauv.) and horseweed ( Conyza canadensis L. Cronq.) were associated with the CTNO system. Although differences in the aboveground weed densities were inconsistent between the tillage systems, the weed seedbank size was greater in the CT system and having a cover crop further increased the seedbank size.